Strategi Pemasaran Program In Vitro Fertilization (Ivf) dengan Metode Segmenting, Targeting, and Positioning dan 4P (Product, Place, Price, Promotion) di Denpasar, Bali - Wirastuti, Ida Ayu; Dewi, Ni Putu Ayu Prima (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2020)
Medical services related to infertility, In Vitro Fertilization (IVF), or often called IVF, are apparently increasingly in demand by the people of Indonesia. This is shown by the continued growth of patients in the country who use medical services related to IVF. Within a year, the growth reached 25%. In fact, the potential market is predicted to reach 200 thousand patients. Bali Royal Hospital is one of the private hospitals located in Denpasar City, where one of the superior services owned by the Hospital is IVF or IVF. Where this IVF program has also been present in several hospitals in Bali. Therefore, an appropriate marketing strategy is needed in order to achieve the desired visit target.